Recognition of various stakeholder interests in company management - Esser, Irene-Marié (University of South Africa, 2008)
Good corporate governance should be the cornerstone of all company management. Directors ought to know in whose interests the company should be managed. This thesis attempts to answer the following question: whose interests must be granted primacy in the management of a company? In chapter 1 it is stated that shareholders' interests are traditionally granted primacy in the management of a company. There has, however, been a shift in public opinion towards recognition of a wider variety of interests that should be considered than only those of the shareholders. These interests include, inter alia, environmental interests and those of the investors, employees and consumers. This thesis thus focuses on the primary stakeholders, namely individual shareholders, creditors, employees, consumers and suppliers. In chapter 2 a theoretical foundation is provided on the nature of a company. The different theories on the nature of a company, emphasising either shareholder primacy or stakeholder protection, are discussed. A combined new theory is proposed. It is suggested that the confusion relating to the meaning of "the company" needs to be eliminated. Chapters 3, 4 and 5 provide an international comparison of the company law in Botswana, Australia, New Zealand and the United Kingdom. The focus falls, firstly, on directors' duties, secondly, on the question in whose interests directors should manage a company and, thirdly, on the codification of their duties. In chapter 6 the South African position is evaluated. First, the possible stakeholders are identified and the protection currently afforded them is explained. The reports of the King Committee on Corporate Governance, the Policy Document on company law reform as well as the Companies Bill of 2007 are discussed. Draft clauses are recommended to be incorporated in new company legislation to provide directors with clarity on what is expected of them. It is the aim of this thesis to provide clarity on whose interests should receive primacy when directors manage a company. The outcome of this research should provide a clear indication to South African directors of what is expected of them and who the beneficiaries of their fiduciary duties are.
Keywords: Codes of best practice; Consumers; Corporate governance; Corporation law; Creditors; Directors' Duties; Shareholder value; Shareholders; Social responsibility of business; Stakeholders

Crossing the Wires: the Interface between Law and Accounting and the Discourse Theory Potential of Telecommunications Regulation - Carter, David Bernard (Victoria University of Wellington, 2008)
Regulating telecommunications is complex: international experience indicates that there is no 'successful' regulatory framework due to the balancing of industry and regulatory interests (Laffont & Tirole, 2000, p. 13). The New Zealand 'light-handed' regulatory experiment failed and the 1999 General Election presented an opportunity for change in telecommunications. The Labour-led Government in implementing a policy of 'responsible re-regulation' enacted the Telecommunications Act 2001, signalling the passage of "landmark telecommunications legislation ..." (Swain, 2001d). Within the Telecommunications Act 2001, 'cost' assumed a central regulatory role. It is this move to cost that this thesis considers in identifying, developing, and critiquing the interface of law and accounting. The thesis examines the increasing call for accounting information in law and regulation by interrogating the use, presentation, and reception of accounting to examine the interface between law and cost in the regulation of telecommunications. The Telecommunications Act 2001 incorporates total service long run incremental costing as the 'costing technique' for interconnection access and annual net costing for the Telecommunications Service Obligation. Through interrogating 'cost' as an accounting technology, in contrast to the economic and legal conception of cost as a simple, objective concept, the thesis illustrates the role of cost at methodological, technical, and political levels, and the challenges that this poses for telecommunications regulation. The thesis articulates the relevance of discourse theory to the interface of law and accounting. Consequently, the thesis investigates the formation and discursive enunciation of standpoints of political identities characterised by antagonism and uncertainty. This includes identifying attempts by interested parties, including industry actors, stakeholders, and the Government and its agents, to articulate 'new' discourses centred on nodal points around 'cost'. The rhetorical analysis examines how actors articulate the metaphorical element of 'cost' in agitating for particular costing methods to be included in the legislation. The empirical analysis examines the process of rhetorical condensation as arguments for and against the incorporation of total service long run incremental costing and net costing came to signify the complete failure of the light-handed regulation. Then, by examining the politics following the enactment of legislation, this condensation is unpacked. The analysis of the contestation over interpreting and implementing the regulation illustrates displacement of the 'common' signifier resulting in confusion and disappointment in relation to the aims of the new regulatory regime.

The development of performance requirements in international law and their effect on BITs and FTAs as well as on the agreeing parties - Bless, Christopher Josef Manfred (Universität Wien, 2008)
Performance requirements are part of a system of policy measures implemented by states to advance their economic, social and political objectives. A universally agreed upon definition of performance requirements is not available. Rather they are defined by the applicable legal norms and their assessment is dependent upon their effect on the parties of each individual case. The scope of legal protection these regulations provide must be measured separately for each norm within the scope of the specific legal framework. This dissertation has two objectives: First, the implementation and legal effect of performance requirements in international investment and trade law are investigated. Secondly, a legal test will be developed, that allows for an assessment of performance requirements. In a first step, the legal treatment of performance requirements will be analyzed from a theoretical perspective. Subsequently, the legal practices relating performance requirements and the relevant provisions in international investment and trade law will be identified. The developed legal test does not only do justice to the economic, social and political framework within which each performance requirement must be looked at but is also adaptable in a way that it can be applied to a variety of situations and legal traditions. It satisfies both the demands of legal certainty and clarity as well as facilitating the finding of justice on an individual basis. Understanding the advantages of foreign direct investment, the analysis performed aims promote the usage of performance requirements in a way that foreign direct investment will push the global economy forward.
Keywords: FIRA; Foreign direct investment; Free trade agreements; International Trade; International investment; Investment treaties; NAFTA; Performance requirements